The Great Book of Music of Al Farabi - A Medieval Model for a Musico-Theoretical Research (De Musica, 2025)
The Great Book of Music (Kitab al-Musiqa al-Kabir), by the Golden Age Islamic philosopher Al-Farabi, is a X th. century treatise on music in Arabic. It consists of two parts, the first being an introduction in which the definition of melody and its subdivisions, the origin of music, and some acoustic problems are discussed. The second part is devoted to the specifics of musical instruments popular among Arabs, the variety of rhythms, and the composition of melodies. Influenced by Pythagoras' theory of harmonic relationships,  Farabi gives us a detailed definition of music, reveals its categories, and describes the elements from which a musical work is formed. The author systematically and subversively explains the importance of induction, and supports his theory emphatically by evidence, asserting that many of the principles he derives are acquired through sense experience, as in astronomy, optics, medicine, and other sciences.
Keywords: music; pedagogy; medieval; eastern; musico-theoretical; philosophy; induction; sensory experience